Experimental study of wake-induced instability of coupled parallel hanger ropes for suspension bridges. (15th July 2018) - Wen, Q.; Hua, X.G.; Lei, X.; Chen, Z.Q.; Niu, H.W.
Highlights: Wake-induced instability of two coupled cylinders was studied for various cylinder spacings. Two coupled cylinders displayed superior aerodynamic behaviors than two separate cylinders. Minimum damping necessary to suppress wake-induced instability was established. The instability mechanism is discussed based on the quasi-steady theoretical model. Aeroelastic model tests were used to evaluate the subspan vibrations. Abstract: Hangers in suspension bridges are usually composed of closely-spaced multiple cables, and they may suffer from server wind-induced vibrations due to the wake interference effect. The primary objective of this research was to examine the wake-induced instability of the coupled twin or quadruple cylinders that are tied together to have the same motion, instead of separate cylinders vibrating independently. The elastically mounted twin cylinders free to oscillate in streamwise and transverse directions were tested at various cylinder spacings. The Scruton (Sc) number, Sc = 2 mδ/ρD 2 ( D is cylinder diameter, δ is logarithmic decrement, m is cylinder mass per unit length, and ρ is fluid density), was varied from about 65–420 by changing the damping, and the critical damping necessary to suppress the wake-induced instability was established. The wake-induced instability occurred with an elliptical orbit at cylinder spacing of 3.2 D and wind incidence angle of 10°, while no instability was found at other spacings. The results of force measurements were presented and used to discuss the excitation mechanism based on the 1-DoF and 2-DoFs quasi-steady model. Despite some differences between theoretical analysis and measurements, the 2-DoFs model outperforms greatly the 1-DoF model in predicting the critical wind speed. For the coupled quadruple cylinders arranged in rectangular configuration, no large amplitude vibrations were found at all wind incidence angles due to complicated flow interference. Finally, the wake-induced instability of hanger subspans divided by spacers was investigated with a new aeroelastic model, and it was found that four spacers placed at equal intervals along hanger length are sufficient to suppress the wind-induced instability within the subspan for hangers in the Xihoumen Bridge.